DEVELOPMENT IN SYNTHESIS AND COATING APPLICATIONS OF POLYURETHANE - Dipti Vaya; Tejpal Singh Chundawat; Nidhi Verma (Journal of the Chilean Chemical Society, 2021)
Polyurethanes as one of the leading elastomers are explored in academics as well as in industry. These are segmented macromolecules having alternate sequence of soft and hard segments. Structure-property correlation between these segments has been extensively reported in the literature. PUs are used widely in coatings, varnishes, glues, foams, adhesives, sealants, automobile parts, synthetic leather etc. Its application in biomedical devices is also growing rapidly. It is therefore need to highlights the recent developments in this fast growing field. The present article is summarized the conventional and ecofriendly synthetic routes for the preparation of PUs. Conventionally, PUs was  synthesized by isocyanates route, later shortcoming of this method explore new synthesis method in which either used biobased polyol or non isocyanates route for preparation of ecofriendly PUs. The applications of different types of PUs coating in various fields are also highlighted in this review.